Problems of digital transformation of laboratory practicum during teaching of natural science disciplines; Journal of Physics: Conference Series; Vol. 1691 : ASEDU-2020: Advances in Science, Engineering and Digital Education - Korshunov A. V. Andrey Vladimirovich (2020, 2020)
Title screen